Study of Planning Problems in the Construction of Small Towns in Southwest - Chen, Yinzhu (International Journal of Social Sciences and Public Administration, 2025)
Today, with the rapid development of China’s economy, China’s urbanization process is also accelerating, and the implementation of the urban-rural integration policy has made the pace of China’s urbanization development faster and faster, The construction of small towns is one of the most important core contents of China’s urbanization system, and at the same time, it is also the first step of accelerating the urbanization process and shortening the difference between urban and rural areas and regions in the southwestern part of China. The state has paid great attention to the construction of small towns, which has created a favorable policy environment for the construction of small towns all over the country. in the process of implementing China’s western development strategy, the construction of small towns has not only promoted the process of China’s agricultural industrialization, but also promoted the process of China’s industrialization in the southwestern region. This paper is in such a background, with the characteristics of Yibin Sichuan Province, small town construction planning as an example, small towns in the southwest region of the problems existing in the planning of in-depth research and analysis, and for these problems put forward the corresponding measures to solve them, l hope to be able to Southwest China’s urban and rural development of the integrated development of a certain degree of reference significance.